Lebanon : 2019 Article IV Consultation-Press Release; Staff Report; Informational Annex; and Statement by the Executive Director for Lebanon. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Lebanon highlights that Lebanon's economic position continues to be very difficult, with very low growth, high public debt and large twin deficits. While financial stability has been maintained, deposit inflows, critical to finance the budget and external deficits, slowed down during the past year, reducing the authorities' room for manoeuvre. The new government has taken some important policy steps to start the needed policy adjustment, which could help raise confidence among investors and donors. The highest priority is the implementation of a sustainable fiscal adjustment that will bend down the path of the public debt-to-gross domestic product ratio through a combination of revenue and expenditure measures. This needs to be complemented by structural reforms and concessionally financed investment to raise Lebanon's growth potential and help external adjustment, as well as policies to build further buffers in Lebanon's financial sector. Structural reforms should prioritize reforming the electricity sector, removing impediments to and lowering the cost of doing business, as well as improving governance and reducing corruption.